Symptomatic intestinal dilation after side-to-side stapled anastomosis during infancy in patients with short bowel syndrome: A case series - Shruthi Srinivas; Andrew Klingele; Katherine C. Bergus; Peter C. Minneci (Elsevier, 2024)
Introduction: In infants undergoing bowel resection, side-to-side stapled anastomosis (SSA) may restore intestinal continuity. We describe cases of abnormal symptomatic intestinal dilation secondary to SSA in patients with short bowel syndrome (SBS). Case presentation: Case 1 is an infant who underwent SSA for meconium ileus. He developed progressive malabsorption and was found to have a dilated segment of 9 by 8 cm at the prior SSA. This was narrowed into two lumens. He continues to gain weight appropriately.Case 2 is an infant with compartment syndrome resulting in partial colectomy and small bowel resection. Continuity was restored with SSA. On abdominal exploration years later for persistent abdominal pain, the area of prior SSA measured 14 by 9 cm and was narrowed into two lumens. He has excelled postoperatively.Case 3 and Case 4 are older patients referred after initial resection and SSAs as infants. Both had adequate intestinal length excluding their dilated areas and underwent resection with redo SSA as young adults. Both continue to do well.Case 5 is an ex-premature boy with neonatal necrotizing enterocolitis and two prior SSAs. He developed chronic pain and underwent resection of dilated intestine with redo SSA. This dilation recurred at the new SSA two years later. He then underwent division back into two lumens. He is now doing well. Conclusion: In patients undergoing bowel resection, SSA can cause abnormal dilatation requiring narrowing. Based on these outcomes, we caution against SSA in patients with anticipated SBS.